Current and experimental therapeutics for Fabry disease. Issue 3 (25th May 2021) - Castelli, Vanessa; Stamerra, Cosimo Andrea; d'Angelo, Michele; Cimini, Annamaria; Ferri, Claudio
Abstract: Fabry (or Anderson‐Fabry) is a rare pan‐ethnic disease affecting males and females. Fabry is an X‐linked lysosomal storage disease, affecting glycosphingolipid metabolism, that is caused by mutations of the GLA gene that codes for α‐galactosidase A. Fabry disease (FD) can be classified into a severe, classical phenotype, most often seen in men with no residual enzyme activity, that usually appear before 18 years and a usually milder, nonclassical (later‐onset) phenotype that usually appear above 18 years. Affected patients show multifactorial complications, including renal failure, cardiovascular problems, and neuropathy. In this review, we briefly report the clinical trials so far performed with the available therapies, and then we focus on the in vitro and the in vivo experimental models of the disease, to highlight the relevance in improving the existing therapeutics and understand the mechanism of this rare disorder. Current available in vivo and in vitro models can assist in better comprehension of the pathogenesis and underlying mechanisms of FD, thus the existing therapeutic approaches can be optimized, and new options can be developed. Abstract : Schematic representation of the pathogenic mechanism that occurs in Fabry disease.